Shaping the Role of sub-Saharan African Nurses and Midwives: Stakeholder's perceptions of the Nurses' and Midwives' tasks and roles - Naomi M. Seboni; Mabel K.M. Magowe; Leana R. Uys; Mary B. Suh; Komba N. Djeko; Haouaou Moumouni (AOSIS, 2013)
To explore the role expectations of different stakeholders in the health care system on the roles and tasks that nurses and midwives perform, in order to clarify and strengthen these roles and shape the future of nursing education and practice in sub-Saharan Africa. Qualitative focus group discussions were held with different stakeholders (nurses, health service managers, patients and their caregivers, community members and leaders and other health professionals) in eight African countries in order to establish their role expectations of nurses and midwives. Three questions about their role expectations and the interviews were taped, transcribed, and translated into English and analysed. There was consensus amongst the stakeholders regarding eight role functions: taking care of patients; giving health information; managing the care environment; advocating for patients; services and policies; providing emergency care; collaborating with other stakeholders; and providing midwifery care to women, infants and their families. There was disagreement amongst the stakeholders about the role of diagnosis and prescribing treatment. Nursing derives its mandate from communities it serves, and the roles expected must therefore form part of nursing regulation, education and practice standards. Health planners must use these as a basis for job descriptions and rewards. Once these are accepted in the training and regulation of nursing, they must be marketed so that recipients are aware thereof. Om die rol verwagtings van verskillende rolspelers in die gesondheidsisteem aangaande die rolle en take van die verpleegkundiges en vroedvroue te ondersoek, om daardeur uitklaring en helderheid en bekragtiging van hierdie rolle te verkry, waardeur die toekoms van verpleeg-onderwys en praktyk in sub-Sahara Afrika gevorm kan word. Kwalitatiewe fokus groepe is met verskillende rolspelers (verpleegkundiges, gesondheidsdiens bestuurders, pasiënte en hulle versorgers, lede van die gemeenskap, leiers en lede van andere gesondheidsprofessies) in agt Afrika lande gehou om hul rolverwagtings van verpleegkundiges en vroedvroue te bepaal. Drie vrae is oor die rolverwagtings gevra. Die onderhoude is opgeneem, getranskribeer, in Engels vertaal, en geanaliseer. Daar was konsensus tussen rolspelers oor agt rol funksies: versorging van pasiënte; die gee van gesondheidsinligting; bestuur van die sorgomgewing; voorspraak vir pasiënte; dienste en beleid; voorsiening van nooddienste; samewerking met ander rolspelers; en voorsiening aan moeder en kindersorg vir vroue en hul gesinne. Ooreenstemming is nie bereik aangaande die rol van diagnose en voorskryf van behandeling nie. Verpleging kry sy mandaat van die gemeenskappe wat gedien word en daarom behoort die rolverwagtings deel te vorm van verpleeg-regulasie, onderwys en praktyk- standaarde. Gesondheidsdiensbeplanners behoort hierdie verwagtings as basis te gebruik vir werksbeskrywings en erkenning. Na die aanvaarding van hierdie verwagtings in verpleegopleiding en regulering, moet dit bekend gemaak word sodat die gemeenskap daarvan bewus is.